Impact of the SAGAL livelihood project on community engagement, economic empowerment, and maternal health service uptake in Galmudug, Somalia - Salad Halane; Mohamed Hussein Muhumed; Mohamed Mustaf Ahmed; Abdiwali Mohamed Ahmed; Jamilu Sani; Rashed Shah; Abdullahi Mohamed Mohamud; Abdullahi Abdulle Farah; Mohamud Isse Yusuf (Discover Public Health)
Abstract Background Maternal health outcomes remain a pressing concern in fragile and conflict-affected settings such as Somalia, where financial and sociocultural barriers exacerbate disparities in access to essential health services. The SAGAL Social Transfers to Vulnerable Somali People project was implemented to address these barriers through cash-based social transfers and integrated community mobilization efforts. This study assesses trends in antenatal care (ANC) and skilled birth attendance (SBA) following the implementation of the SAGAL livelihood project in three hospitals in the Galmudug state of Somalia. Using a retrospective longitudinal approach, the study explores associations between the intervention and service utilization without employing a formal impact evaluation design. Methods This retrospective longitudinal study analyzed health service utilization data of 6,582 pregnant and lactating women who accessed ANC or SBA services at three health facilities (Adado, Herale, and Hurshe) between September 2021 and October 2023. Data were extracted from facility registers, monthly reports, and the DHIS2 system. Descriptive statistics and trend analyses were used to evaluate changes in service uptake before and after the intervention. Results In the urban areas ANC utilization has increased considerably from 28% in 2021 to 86% in 2022, with a slight decline to 75% by 2023. The prevalence of SBA has increased from 8% in 2021 to 27% in 2022, stabilizing at 25% by 2023. Adado showed the highest SBA uptake (34%), whereas the rural area such as Hurshe reported the lowest uptake (8%). The observed trends suggest a positive impact of the SAGAL intervention on service utilization. Facilities in urban areas such as Adado experienced a marked increase in SBA and ANC uptake, while rural areas such as Hurshe showed relatively slower progress, indicating variability in program implementation or local barriers. Seasonal variations and community engagement intensity influenced service utilization trends. Conclusion The SAGAL project considerably improved maternal health service utilization in the studied facilities, particularly for ANC and SBA. Sustaining these gains requires continued investment in health infrastructure, strengthened referral pathways, and adaptive community mobilization strategies. This study underscores the potential of integrating economic empowerment initiatives with health-service delivery to improve maternal health outcomes in fragile contexts.